FAKTOR-FAKTOR YANG MEMPENGARUHI OPINI AUDIT GOING CONCERN - Krissindiastuti, Monica; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 14 No 1 (2016), 2016)
This research enhances and examine about the effect of audit tenure, company growth, firm size, KAP’s reputation, opinion shopping, and the previous audit opinion towards audit going concern opinion. The sample of this research is obtainable by using the purposive sampling method by focusing on manufacture companies that has been listed on the Indonesia Stock Exchange, 2010-2013. Samples were obtained as many as 12 companies by the number of observations is 48 sample. Data analysis techniques used in this research is the logistic regression analysis techniques. Based on the analysis results it is revealed that the audit tenure, company growth negative affect towards the going concern audit opinion. KAP’s  reputation and opinion shopping positive affect towards the going concern audit opinion. Therefore, the firm size and previous audit opinion doesn’t seet to affect towards the going concern audit opinion.
Keywords: Audit Tenure; Company Growth; Firm Size; KAP' s Reputation; Opinion Shopping; Previous Audit Opinion; Going Concern Audit Opinion